(untitled) (American Journal of Islam and Society, 2023)
David H. Warren enriches the rising literature on ʿulamaʾ and the “Arab Spring” with his first book, which provides an overview of the history of Yusuf al-Qaradawi and Abdullah Bin Bayyah’s relations with Qatar and the UAE, respectively; both ʿulamaʾ and states’ engagement with the “Arab Spring”; and the political thought of both ʿulamaʾ and its connection to both states’ foreign policy. After describing the book’s structure here, I discuss the book’s methods and core arguments. I then engage methodologically with some of its arguments and conclude with why this book is a good model for scholarship on the ʿulamaʾ.